Rural Research and Development Corporations' Connection to Agricultural Industry School Partnerships - Molly O'Dea; Amy Cosby; Jaime K. Manning; Nicole McDonald; Bobby Harreveld (MDPI AG, 2024)
The Australian Government has prioritized science, technology, engineering, and mathematics (STEM) education in recent years to ensure that the country has an adequate future workforce. The agriculture industry is a major employer with a diverse range of occupations heavily focused on STEM. Many students do not realize the career opportunities in the sector, which is currently facing severe workforce shortages. Industry school partnerships (ISPs) have been identified as one creative model to improve students' knowledge of an industry and aspirations for associated careers. Whilst ISPs have been implemented in the STEM context, limited research understands how industry organizations are involved in, influence, and interconnect with ISPs. Australia's Rural Research and Development Corporations (RRDCs) are legislated agricultural industry bodies and were selected to investigate due to the value ISPs could provide to this STEM-focused industry with workforce shortages. This qualitative case study analyzed data from the most current RRDC strategic and annual operating plans as of 27 July 2023 and semi-structured interviews with an employee(s) in a position relevant to student education of all 15 RRDCs in 2022. The key findings were that ISPs were considered part of the solution to address industry sustainability, though RRDCs were commonly only informally involved. Collaboration between industry partners, facilitators, and teachers at strategic and management levels and across commodities was essential. RRDCs were found to be strongly connected to ISP ecosystems through their role in research and development. We argue that RRDCs are positioned as essential stakeholders with the scope to improve agricultural ISP ecosystems as part of their role in driving agricultural innovation. These findings support the application of ecological systems theory to agricultural ISPs and help us to understand these structures. This paper aims to help those creating ISPs to consider and understand all stakeholders, including industry bodies, to deliver quality future partnerships that benefit both STEM sectors and primary and secondary student education.